M1 Muscarinic Receptor Activation Rescues β-Amyloid-Induced Cognitive Impairment through AMPA Receptor GluA1 Subunit. (1st June 2019) - Zhao, Lan-Xue; Chen, Mu-Wen; Qian, Yue; Yang, Qian-Hao; Ge, Yan-Hui; Chen, Hong-Zhuan; Qiu, Yu
Abstract: M1 muscarinic receptors have long been identified as a potential therapeutic target for the treatment of cognitive impairment in Alzheimer's disease (AD). Our previous study has shown that M1 receptors promote membrane insertion and synaptic delivery of AMPA receptor GluA1 subunit. In this study, we sought to determine whether activation of M1 receptor would rescue the cognitive impairment in AD model mice through modulation of GluA1 subunit. For the mice injected with aggregated β-amyloid (Aβ) fragments to impair learning and memory, activation of M1 receptors could rescue it by reducing the latency to find the platform and spending more time in the target quadrant in the probe test in the Morris water maze. However, such an effect was ablated in mice with Ser845 residue of GluA1 mutated to alanine. Furthermore, the activation of M1 receptors enhanced the expression of GluA1 and its phosphorylation at Ser845 and drove GluA1 to incorporate with PSD95, a postsynaptic marker, in the hippocampi from Aβ-injected wild type mice but not from the mutant mice. Moreover, for 9-month-old APP/PS1 transgenic AD model mice, which may resemble the late AD, M1 receptor activation could not improve the cognitive impairment significantly. In addition, the enhancement of GluA1 expression and its phosphorylation at Ser845 were not observed in their hippocampi. Taken together, the study indicated that M1 receptor activation rescued the cognitive deficit through modulating the trafficking of GluA1-containing AMPA receptors and the therapeutics targeting M1 receptors should aim at mild AD or even pre-AD. Highlights: M1 receptor activation rescues Aβ-induced cognitive impairment in wild type mice but not in GluA1 S845A mutant mice. Chronic activation of M1 receptors enhances the expression of GluA1 through its phosphorylation at Ser845. M1 receptor activation does not significantly improve learning and memory in 9-month APP/PS1 mice. The potential therapeutics targeting M1 receptors may be appropriate for early AD or even pre-AD.